Equine Degenerative Myeloencephalopathy - De Fátima Dallo, Bianca; Xavier Ribeiro da Silva, Larissa; Aparecida Oliveira de Paula, Liliane; Freitas Pereira e Silva, Nathany; Smaniotto, Crisan; Maciel Pagliosa, Geane; de Marco Viott, Aline; de Cássia Seudo Lopes, Maristela (Acta Scientiae Veterinariae, 2023)
Background: Equine degenerative myeloencephalopathy (EDM) is a neurodegenerative disease that appears to be associated with an early deficiency of vitamin E and suspected genetic inheritance. However, other causes such as scarce or low-quality pastures and intoxication by pyrethrins or pyrethroids have already been reported. Equine degenerative myeloencephalopathy has already been described in several breeds; there is no predisposition by sex, and foals up to 2 years of age are the most affected animals. The objective of this study is to report the case of an adult mare with EDM as well as clinical and histopathological features of the disease and the main differential diagnoses. Case: A 10-year-old, 400 kg Quarter Horse (QH) mare presented with nonspecific neurological signs such as proprioception deficit and progressive asymmetric ataxia of the hindlimbs with a 3-month evolution. The hypothesis of traumatic injury was firstly considered, after a history of having been subjected to natural mating for reproduction; nonetheless, after being subjected to a stressful condition (vulvoplasty), upon the main complaint of the owner, there was worsening of the ataxia and the ability to stand by itself. Considering the stressful condition of the procedure, the clinical suspicion was directed towards Equine Protozoal Myeloencephalitis (EPM). Because of the impossibility of collecting cerebrospinal fluid for serology and performing imaging tests, anticoccidial therapy was started (manipulated Diclazuril paste) for 30 days, with the objective of obtaining a therapeutic diagnosis. In addition, supportive therapies, physiotherapy, and rehabilitation were maintained throughout the hospitalization period. Due to the lack of clinical improvement, the owner opted for euthanasia. Necropsy was performed and central nervous system samples were collected, for histopathological evaluation. Besides that, fragments of brain and thalamus were sent to the official laboratory. Macroscopically, there were no medullary and brain alterations, whereas microscopy showed areas of axon degeneration and spongiosis involving the white matter and gray matter in the cervicothoracic segments and in the brainstem, specifically in the tectospinal, reticulospinal, anterior spinocerebellar, and dorsal spinocerebellar tracts and gracile and cuneiform fasciculi, confirming the diagnosis of EDM. Discussion: This is the 1st reported case of EDM in Brazil, there being only one report of its variant in a mule. In the case, manifestations appeared at 10 years of age and the presented ataxia was asymmetrical with pivoting on the left limb, contrary to that reported in the literature. Histopathological examination revealed a showed areas of axonal degeneration with formation of spheroids, characteristic lesional pattern of EDM, however, the left antimere of the evaluated segments was slightly more affected. Among the causes mentioned for the development of the disease, the hereditary or breed factor in this case cannot be ruled out. In an American study, horses diagnosed with EDM (38/265) were 2.95 times more likely to be a Quarter Horses. The nonspecific and varied clinical presentation of EPM makes it the main differential diagnosis for EDM, but other neurological diseases must also be ruled out. Given this assumption, EDM should be considered as a differential diagnosis in QH of all ages that present with proprioceptive ataxia of medullary origin. Keywords: ataxia, neurological disorder, neuroaxonal dystrophy, spheroids. Título: Mieloencefalopatia degenerativa equina Descritores: ataxia, desordem neurológica, distrofia neuroaxonal, esferoide.